AN INTEGRATED DEMATEL-IF-TOPSIS METHODOLOGY FOR LOGISTICS CENTERS' LOCATION SELECTION PROBLEM: AN APPLICATION FOR ISTANBUL METROPOLITAN AREA - Uyanik, Cihan; Tuzkaya, Gulfem; Kalender, Zeynep Tugce; Oguztimur, Senay (VILNIUS GEDIMINAS TECH UNIV, 2020)
Logistics Centers (LCs) are among the most important facilities for rapid, cost effective, environmental friendly and secure logistics services to the urban logistics problems. Finding proper locations to LCs has an important effect on their success. In this study, LCs' location selection problem for Istanbul Metropolitan area is investigated. Istanbul is a leading city of Turkey in many categories including various industries, import/export amounts, transportation infrastructure and population density. However, industrialization and urbanization have introduced numerous problems to Istanbul. New projects are continuously being announced for the problems of metropolis, however, they may also bring new problems if they are not punctiliously planned and applied. Hence, in this study, it is aimed to propose a systematic Multi-Criteria Decision-Making (MCDM) approach for the LCs' location selection problem of Istanbul. In this approach, an integrated DEcision-MAking Trial and Evaluation Laboratory (DEMATEL) and Intuitionistic Fuzzy (IF) Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method is utilized. DEMATEL is used to analyse the decision criteria and IF-TOPSIS is used to evaluate candidate locations for LCs. Considering the vagueness inherent to this decision-making problem, IF sets are used for the evaluation process. Results are compared with the results of IF-VIKOR (VIse Kriterijumska Optimizacija kompromisno Resenje - multi-criteria optimization and compromise solution) technique.
Keywords: logistics centers; DEMATEL; intuitionistic fuzzy sets; TOPSIS; location selection; FUZZY; DECISION; MODEL; Transportation